ETHICAL HORIZONS: A COMPREHENSIVE EXPLORATION OF CONTEMPORARY BUSINESS ETHICS PRACTICES - Sheikh, Rashel; Sabur, Md. Abdus; Sina, Md. Abu (International Journal of Research -GRANTHAALAYAH, 2024)
This paper provides a comprehensive analysis of business ethics practices from 2014 to 2023 against the backdrop of a rapidly changing socio-economic landscape. Recognizing the escalating global challenges, the study employs the PRISMA framework to scrutinize 60 selected articles out of 1023 database entries. Examining business ethics through various lenses, the paper categorizes articles by year, country, continent, and subject groups. Initial emphasis on business ethics and Human Resource Management underscores the global impact of leadership, governance, and ethical interventions in maintaining standards. Noteworthy findings highlight NGOs’ role in promoting ethical considerations in HRM practices. Leadership, codes of ethics and transparency emerge as pivotal factors in fostering sound business ethics. The study further explores the intersection of business ethics and marketing, emphasizing ethical practices’ role in influencing consumer confidence, organizational performance, and brand image. The interconnectedness of business ethics and sustainability challenges the perception of associated costs, advocating for ethical rule integration in Small and Medium Enterprises. Additionally, the paper delves into the incorporation of Islamic principles into business ethics, showcasing their potential to transform businesses into socially responsible entities.